Liquid Viscosity and Surface Tension of n-Hexane, n-Octane, n-Decane, and n-Hexadecane up to 573 K by Surface Light Scattering - Klein, Tobias; Yan, Shaomin; Cui, Junwei; Magee, Joseph W.; Kroenlein, Kenneth; Rausch, Michael Heinrich; Koller, Thomas Manfred; Fröba, Andreas Paul (Journal of Chemical and Engineering Data, 2019)
In the present study, the simultaneous and accurate determination of liquid viscosity and surface tension of the n-alkanes n-hexane (n-C6H14), n-octane (n-C8H18), n-decane (n-C10H22), and n-hexadecane (n-C16H34) by surface light scattering (SLS) in thermodynamic equilibrium is demonstrated. Measurements have been performed over a wide temperature range from 283.15 K up to 473.15 K for n-C6H14, 523.15 K for n-C8H18, and 573.15 K for n-C10H22 and n-C16H34. The liquid dynamic viscosity and surface tension data with average total measurement uncertainties (k = 2) of 2.0 and 1.7% agree with the available literature and contribute to a new database at high temperatures. Over the entire temperature range, a Vogel-type equation for the dynamic viscosity and a modified van der Waals equation for the surface tension represent the measured data for the four n-alkanes within experimental uncertainties. By also considering our former SLS data for n-dodecane (n-C12H26) and n-octacosane (n-C28H58), empirical models for the liquid viscosity and surface tension of n-alkanes were developed as a function of temperature and carbon number covering values between 6 and 28. Agreement between these models and reference correlations for additional selected n-alkanes, which were not included in the development procedure, was found.
CRIS-Team Scopus Importer:2019-10-15